Fast ion conductor coated sodium ion battery manganese-based positive electrode material and preparation method thereof
By coating the manganese-based positive electrode material of sodium ion battery by fast ion conductor, the problem of reaction between sodium ion battery materials and electrolytes is solved, and the structural stability and electrochemical performance of the material are improved.
Patent Information
- Application Number
- CN202411953215.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
Sodium ion battery materials are prone to react with electrolytes during charging and discharging, resulting in structural instability and limited performance.
Fast ion conductor is used to coat the manganese-based positive electrode material of sodium ion battery, and the ZnxMgyMn1-x-yCO3 precursor is synthesized through co-precipitation reaction, and react with the sodium source under high temperature conditions to form a sodium metaaluminate coating layer to reduce direct reaction with the electrolyte.
It effectively suppresses the direct reaction between the positive electrode material and the electrolyte, improves the ionic conductivity and electrochemical stability of the material, and improves the rate performance and cycle stability of the battery.
Smart Images

Figure CN119725482A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a fast ion conductor coated sodium ion battery manganese-based positive electrode material and a preparation method thereof. Background Art
[0002] The booming electric vehicle market and the growing need for large-scale energy storage make the development of low-cost and high-performance rechargeable batteries more important than at any time in history.
[0003] In recent years, the large-scale energy storage market has flourished, and the new energy vehicle industry has developed rapidly. Its power battery materials are mainly lithium batteries, but the scarcity of lithium resources is threatening its sustainable development. Compared with lithium-ion batteries, sodium-ion batteries play the role of substitutes in the new energy industry due to their low cost and abundant and easy-to-obtain Na resources. It is expected to be the first to replace and apply lithium-ion batteries in energy storage, low-speed transportation, and some low-range passenger cars that do not require high energy density and are highly cost-sensitive. At the same time, the electrochemical performance of sodium-ion batteries is relatively stable, and they are easily passivated and deactivated during thermal runaway, and their safety test performance is better than that of lithium batteries. However, since the radius of sodium ions is larger than that of lithium ions, there are multiple complex phase changes during the charging and discharging process of the material, the structure is unstable, and it is easy to react with the electrolyte. These factors have limited sodium-ion battery materials.
[0004] In the prior art, structural modification is often used to improve the performance of sodium ion batteries, which can reduce the side reactions of sodium ion electrodes and improve the materials from a structural perspective. However, the internal structural modification method can only solve the problem of unstable internal structure of sodium ion battery materials, and cannot solve the problem of reaction between sodium ions and electrolytes. Summary of the invention
[0005] The object of the present invention is to provide a fast ion conductor coated sodium ion battery manganese-based positive electrode material and a preparation method thereof, so as to solve the problem of reaction between sodium ions and electrolytes;
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a fast ion conductor coated manganese-based positive electrode material for a sodium ion battery comprises the following steps:
[0008] S1. Synthesis of Precursors:
[0009] Based on the coprecipitation reaction, soluble manganese salt, soluble zinc salt and soluble magnesium salt are weighed according to the molar ratio of the elements and dissolved in a buffer solution, a precipitant is added and mixed evenly, and after heating the reaction for a period of time, centrifugation is allowed to stand to obtain a yellowish Zn x Mg y Mn 1-x-yCO3 precursor, where x and y correspond to the molar ratio of the elements, and the charge balance and stoichiometric conservation are satisfied between the elements in the chemical formula;
[0010] S2. Coating treatment:
[0011] Weigh aluminum salt as the aluminum source for surface coating, dissolve it in deionized water to obtain an aluminum source solution, and then weigh a certain amount of Zn x Mg y Mn 1-x-y The CO3 precursor is stirred evenly in the aluminum source solution to form a dispersed suspension, and then the mixture is heated and stirred to react for a certain period of time. After the reaction is completed, the mixture is filtered and dried to obtain a coated and modified precursor.
[0012] S3. High temperature roasting:
[0013] The coated modified precursor and the sodium source were evenly ground in a mortar, placed in a corundum calcining boat, and calcined at a specific temperature and atmosphere for a certain period of time to obtain a fast ion conductor coated sodium ion battery manganese-based positive electrode material with a chemical formula of NaAlO2@Na 0.67 Zn x Mg y Mn 1-x-y O2.
[0014] As a further embodiment of the present invention, the manganese salt in S1 is manganese acetate, manganese sulfate or manganese chloride; the zinc salt is zinc acetate or zinc chloride; and the magnesium salt is magnesium acetate or magnesium chloride.
[0015] As a further embodiment of the present invention, the precipitant in S1 is sodium carbonate or sodium bicarbonate.
[0016] As a further embodiment of the present invention, the molar amount of the precipitant is 1 to 2 times the total molar amount of the manganese salt, the zinc salt and the magnesium salt.
[0017] As a further solution of the present invention, the buffer solution in S1 is a citric acid-sodium citrate buffer solution with a pH value of 4.8 to 5.2.
[0018] As a further solution of the present invention, the heating temperature of the heating reaction in S1 and S2 is 50-60° C., and the reaction time is 2-8 hours.
[0019] As a further solution of the present invention, the aluminum source in S2 is aluminum chloride or aluminum sulfate.
[0020] As a further solution of the present invention, the aluminum source in S2 and Zn x Mg y Mn 1-x-y The dosage ratio of CO3 precursor is 0.5-1.5mmol:1g.
[0021] As a further embodiment of the present invention, the sodium source in S3 is sodium carbonate or sodium bicarbonate.
[0022] As a further solution of the present invention, the amount of the sodium source in S3 is 1.02-1.08 times the amount of the coated modified precursor.
[0023] As a further solution of the present invention, the calcination temperature in S3 is 700-800° C., the calcination time is 5-20 hours, and the calcination atmosphere is high-purity oxygen.
[0024] As a further solution of the present invention, the heating rate during the calcination process is 1 to 10°C / min.
[0025] A fast ion conductor coated sodium ion battery manganese-based positive electrode material is prepared by the above preparation method.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention provides a fast ion conductor coated sodium ion battery manganese-based positive electrode material, using sodium aluminate as a fast ion conductor coating layer, sodium carbonate or sodium bicarbonate as a sodium source, and Zn synthesized by coprecipitation reaction x Mg y Mn 1-x-y CO3 precursors are mixed and treated at high temperature to prepare a new type of sodium ion battery positive electrode material. The material is co-doped by doping zinc and magnesium elements in manganese-based oxides at the precursor end. The addition of zinc and magnesium makes it have a wider lattice spacing, reducing the Na + Diffusion is hindered during the charge and discharge process; the sodium aluminate formed on the surface of the material is evenly distributed, which inhibits the direct reaction of the positive electrode material with the electrolyte during the charge and discharge process; at the same time, the fast ion conductor coating layer can also improve the ion conductivity of the material and enhance the rate performance. The sodium ion battery positive electrode material prepared by the method of the present invention has a spherical morphology, good ion diffusion channels and excellent electrochemical stability.
[0028] 2. The present invention first coats the surface of the manganese-based positive electrode material with porous alumina, and then reacts with a sodium source under high temperature conditions to generate sodium aluminate, a fast ion conductor. In addition, the sodium source reacts with Zn x Mg y Mn 1-x-yThe CO3 precursor is doped with elements to obtain a manganese-based positive electrode material coated with sodium aluminate. This method reduces the defectivity of the material, reduces the direct contact between the active material and the electrolyte, and greatly improves the ionic and electronic conductivity of the electrode, thereby improving the electrochemical performance of the lithium-ion battery. At the same time, the sodium aluminate coating in the fast ion conductor (NaAlO2)-coated sodium ion battery positive electrode material is dense and uniform, with a good stable structure, which can effectively inhibit the corrosion of the electrolyte to the positive electrode active material, increase the insertion and extraction rate of sodium ions during the charge and discharge process, improve the cycle stability of the sodium ion battery, and improve the rate performance. The electronic conductivity of the material is improved by element doping, thereby improving the rate performance.
[0029] 3. The fast ion conductor layer coated lithium ion battery positive electrode material of the present invention is prepared by a method of low-temperature synthesis of precursor materials combined with high-temperature sintering. This method has low raw material cost, simple operation and environmental friendliness, and overcomes the shortcomings of traditional fast ion conductor coating modification methods such as high raw material cost, complex operation process and cumbersome process. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention will be further described below in conjunction with the accompanying drawings.
[0031] Figure 1 It is a process flow diagram of a method for preparing a fast ion conductor coated manganese-based positive electrode material for a sodium ion battery according to the present invention;
[0032] Figure 2 is a scanning electron microscope (SEM) image of the coated and modified precursor in Example 1 of the present invention;
[0033] Figure 3 This is a SEM image of the fast ion conductor coated sodium ion battery manganese-based positive electrode material obtained after high-temperature calcination in Example 1 of the present invention;
[0034] Figure 4 is a comparison chart of the discharge capacity of the battery prepared in Example 1 of the present invention and the battery prepared in Comparative Example 1 after 50 cycles at a rate of 0.1C;
[0035] Figure 5 It is a comparison chart of the discharge capacity of the battery prepared in Example 1 of the present invention and the battery prepared in Comparative Example 2 after 100 cycles at a 1C rate. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Unless otherwise specified, the heating rate parameter in the heating reaction process of the present invention is adjusted automatically according to the temperature set by the heating equipment used; the stirring speed parameter is not particularly limited as long as it meets the industry standard. In the following embodiments and comparative examples, the stirring speed is selected as 200 rpm.
[0038] See also Figure 1 , a method for preparing a fast ion conductor coated manganese-based positive electrode material for a sodium ion battery, comprising the following steps:
[0039] S1. Synthesis of Precursors:
[0040] Based on the coprecipitation reaction, soluble manganese salt, zinc salt and magnesium salt are weighed according to the molar ratio of the elements and dissolved in a buffer solution (citric acid-sodium citrate buffer solution, pH value is 4.8-5.2) to form solution A, and stirred for reaction at room temperature (25-30°C) for 2-3 hours; the precipitant is weighed and dissolved in deionized water to prepare a precipitant solution (the molar amount of the precipitant is 1-2 times the total molar amount of the manganese salt, zinc salt and magnesium salt); the precipitant solution is quickly poured into solution A, stirred for reaction at a heating temperature of 50-60°C for 6-8 hours, centrifuged and collected to obtain a yellowish brown precipitate, which is thoroughly washed with deionized water and anhydrous ethanol, and dried in an oven at 80°C. Zn x Mg y Mn 1-x-y CO3 precursor;
[0041] S2. Coating treatment:
[0042] Weigh aluminum salt as the aluminum source for surface coating, dissolve it in deionized water to obtain an aluminum source solution, and then x Mg y Mn 1-x-y CO3 precursor 0.5 ~ 1.5mmol: 1g dosage ratio, weigh a certain mass of Zn x Mg y Mn 1-x-y The CO3 precursor is added to the aluminum source solution, dispersed by stirring to form a uniform suspension, and then continued to stir and react for 6 to 8 hours under heating conditions of 50 to 60°C. After the reaction is completed, it is centrifugally washed several times with deionized water and anhydrous ethanol, and placed in an oven at 90°C to obtain a coated modified precursor;
[0043] S3. High temperature roasting:
[0044] The coated modified precursor and the sodium source are weighed according to the dosage ratio of 1g:1.02-1.08g (i.e., the sodium source is 2% to 8% in excess), the coated modified precursor and the sodium source are ground and mixed evenly in a mortar, placed in a corundum calcining boat, and uniformly heated from room temperature to 700-800°C at a heating rate of 1-10°C / min, and calcined at 700-800°C in a pure oxygen atmosphere for 5-20h to obtain a fast ion conductor coated sodium ion battery manganese-based positive electrode material, the chemical formula of which is NaAlO2@Na 0.67 Zn x Mg y Mn 1-x- y O2.
[0045] Example 1
[0046] A method for preparing a fast ion conductor coated manganese-based positive electrode material for a sodium ion battery comprises the following steps:
[0047] S1. Synthesis of Precursors:
[0048] 7 mmol of tetrahydrate manganese acetate, 1.5 mmol of dihydrate zinc acetate and 1.5 mmol of tetrahydrate magnesium acetate (the molar ratio of the elements is 0.7:0.15:0.15) are dissolved in 80 mL of buffer solution (citric acid-sodium citrate buffer solution, pH value is 4.8-5.2) to form solution A, and the solution is stirred for reaction for 2.5 h at room temperature; 15 mmol of anhydrous sodium carbonate (the molar amount of the precipitant is 1.5 times the total molar amount of manganese salt, zinc salt and magnesium salt) is weighed and dissolved in 120 mL of deionized water to prepare a precipitant solution, and the precipitant solution is quickly poured into solution A, and the solution is stirred for reaction at a heating temperature of 55°C for 7 h, and the solution is centrifuged to collect a yellowish brown precipitate, which is thoroughly washed with deionized water and anhydrous ethanol, and dried in an oven at 80°C to obtain Zn 0.15 Mg 0.15 Mn 0.7 CO3 precursor;
[0049] S2. Coating treatment:
[0050] Weigh 1 mmol of AlCl3·6H2O and dissolve it in 100 mL of deionized water to obtain aluminum chloride solution. Then weigh 1 g of Zn 0.15 Mg 0.15 Mn 0.7 The CO3 precursor was added to the aluminum chloride solution and dispersed by stirring to form a uniform suspension, and then continued to stir and react for 7 hours under heating conditions of 55°C. After the reaction, it was centrifuged and washed several times with deionized water and anhydrous ethanol, and dried in an oven at 90°C to obtain a coated modified precursor, which was characterized by scanning electron microscopy, such as Figure 2 As shown, it can be seen that the precursor presents a spherical morphology;
[0051] S3. High temperature roasting:
[0052] The coated modified precursor and sodium bicarbonate were weighed in a ratio of 1g:1.05g, the coated modified precursor and sodium bicarbonate were ground and mixed evenly in a mortar, placed in a corundum calcining boat, and heated from room temperature to 750°C at a heating rate of 5°C / min, and calcined at 750°C in a pure oxygen atmosphere for 12h to obtain a fast ion conductor coated sodium ion battery manganese-based positive electrode material with a chemical formula of NaAlO2@Na 0.67 Zn 0.15 Mg 0.15 Mn 0.7 O2 (abbreviated as NaAlO2@NMZMO), and characterized by scanning electron microscopy, such as Figure 3 shown.
[0053] Example 2
[0054] A method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material, which is different from Example 1 in that the molar amount of AlCl3·6H2O in S2 is 0.5 mmol, and specifically comprises the following steps:
[0055] S1. Synthesis of Precursors:
[0056] 7 mmol of manganese acetate tetrahydrate, 1.5 mmol of zinc acetate dihydrate and 1.5 mmol of magnesium acetate tetrahydrate (the molar ratio of the elements is 0.7:0.15:0.15) are weighed and dissolved in 80 mL of buffer solution (citric acid-sodium citrate buffer solution, pH value is 4.8-5.2) to form solution A, and stirred for reaction for 2.5 h at room temperature; 15 mmol of anhydrous sodium carbonate (the molar amount of the precipitant is 1.5 times the total molar amount of manganese salt, zinc salt and magnesium salt) is weighed and dissolved in 120 mL of deionized water to prepare a precipitant solution, and the precipitant solution is quickly poured into solution A, stirred for reaction at a heating temperature of 55°C for 7 h, and centrifuged to collect a yellowish brown precipitate, which is thoroughly washed with deionized water and anhydrous ethanol, and dried in an oven at 80°C. Zn 0.15 Mg 0.15 Mn 0.7 CO3 precursor;
[0057] S2. Coating treatment:
[0058] Weigh 0.5mmol of AlCl3·6H2O and dissolve it in 100mL of deionized water to obtain aluminum chloride solution. Then weigh 1g of Zn 0.15 Mg 0.15 Mn 0.7The CO3 precursor was added to the aluminum chloride solution, dispersed by stirring to form a uniform suspension, and then continued to stir and react for 7 hours under heating conditions of 55°C. After the reaction was completed, it was centrifugally washed several times with deionized water and anhydrous ethanol, and dried in an oven at 90°C to obtain a coated modified precursor;
[0059] S3. High temperature roasting:
[0060] The coated modified precursor and sodium bicarbonate were weighed in a ratio of 1g:1.05g, the coated modified precursor and sodium bicarbonate were ground and mixed evenly in a mortar, placed in a corundum calcining boat, and heated from room temperature to 750°C at a heating rate of 5°C / min, and calcined at 750°C in a pure oxygen atmosphere for 12h to obtain a fast ion conductor coated sodium ion battery manganese-based positive electrode material with a chemical formula of NaAlO2@Na 0.67 Zn 0.15 Mg 0.15 Mn 0.7 O2.
[0061] Example 3
[0062] A method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material, which is different from Example 1 in that the molar amount of AlCl3·6H2O in S2 is 1.5 mmol, and specifically comprises the following steps:
[0063] S1. Synthesis of Precursors:
[0064] 7 mmol of manganese acetate tetrahydrate, 1.5 mmol of zinc acetate dihydrate and 1.5 mmol of magnesium acetate tetrahydrate (the molar ratio of the elements is Mn: Zn: Mg = 0.7: 0.15: 0.15) are weighed and dissolved in 80 mL of buffer solution (citric acid-sodium citrate buffer solution, pH value is 4.8-5.2) to form solution A, and stirred for reaction for 2.5 h at room temperature; 15 mmol of anhydrous sodium carbonate (the molar amount of the precipitant is 1.5 times the total molar amount of manganese salt, zinc salt and magnesium salt) is weighed and dissolved in 120 mL of deionized water to prepare a precipitant solution, and the precipitant solution is quickly poured into solution A, and stirred for reaction at a heating temperature of 55°C for 7 h, and centrifuged to collect the khaki precipitate, which is thoroughly washed with deionized water and anhydrous ethanol, and dried in an oven at 80°C. 0.15 Mg 0.15 Mn 0.7 CO3 precursor;
[0065] S2. Coating treatment:
[0066] Weigh 1.5mmol of AlCl3·6H2O and dissolve it in 100mL of deionized water to obtain aluminum chloride solution. Then weigh 1g of Zn 0.15 Mg0.15 Mn 0.7 The CO3 precursor was added to the aluminum chloride solution, dispersed by stirring to form a uniform suspension, and then continued to stir and react for 7 hours under heating conditions of 55°C. After the reaction was completed, it was centrifugally washed several times with deionized water and anhydrous ethanol, and dried in an oven at 90°C to obtain a coated modified precursor;
[0067] S3. High temperature roasting:
[0068] The coated modified precursor and sodium bicarbonate were weighed in a ratio of 1g:1.05g, the coated modified precursor and sodium bicarbonate were ground and mixed evenly in a mortar, placed in a corundum calcining boat, and heated from room temperature to 750°C at a heating rate of 5°C / min, and calcined at 750°C in a pure oxygen atmosphere for 12h to obtain a fast ion conductor coated sodium ion battery manganese-based positive electrode material with a chemical formula of NaAlO2@Na 0.67 Zn 0.15 Mg 0.15 Mn 0.7 O2.
[0069] Example 4
[0070] A method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material, which differs from Example 1 in that manganese salt, zinc salt and magnesium salt are weighed according to an element molar ratio of Mn:Zn:Mg=0.8:0.1:0.1, and the remaining steps and parameters remain the same.
[0071] Example 5
[0072] A method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material, which differs from Example 1 in that manganese salt, zinc salt and magnesium salt are weighed according to an element molar ratio of Mn:Zn:Mg=0.6:0.1:0.2, and the remaining steps and parameters remain the same.
[0073] Comparative Example 1
[0074] A method for preparing a manganese-based positive electrode material for a sodium ion battery, which is different from that of Example 1 in that Zn is not 0.15 Mg 0.15 Mn 0.7 The CO3 precursor is subjected to coating modification treatment, which specifically includes the following steps:
[0075] S1. Synthesis of Precursors:
[0076] 7 mmol of manganese acetate tetrahydrate, 1.5 mmol of zinc acetate dihydrate and 1.5 mmol of magnesium acetate tetrahydrate (the molar ratio of the elements is 0.7:0.15:0.15) are weighed and dissolved in 80 mL of buffer solution (citric acid-sodium citrate buffer solution, pH value is 4.8-5.2) to form solution A, and stirred for reaction for 2.5 h at room temperature; 15 mmol of anhydrous sodium carbonate (the molar amount of the precipitant is 1.5 times the total molar amount of manganese salt, zinc salt and magnesium salt) is weighed and dissolved in 120 mL of deionized water to prepare a precipitant solution, and the precipitant solution is quickly poured into solution A, stirred for reaction at a heating temperature of 55°C for 7 h, and centrifuged to collect a yellowish brown precipitate, which is thoroughly washed with deionized water and anhydrous ethanol, and dried in an oven at 80°C. Zn 0.15 Mg 0.15 Mn 0.7 CO3 precursor;
[0077] S2. High temperature roasting:
[0078] Zn 0.15 Mg 0.15 Mn 0.7 The CO3 precursor and sodium bicarbonate were weighed in a ratio of 1g:1.05g. 0.15 Mg 0.15 Mn 0.7 The CO3 precursor and sodium bicarbonate were ground and mixed evenly in a mortar, placed in a corundum calcining boat, and heated from room temperature to 750°C at a rate of 5°C / min. The material was calcined at 750°C in a pure oxygen atmosphere for 12 h to obtain a manganese-based positive electrode material for sodium ion batteries with a chemical formula of Na 0.67 Zn 0.15 Mg 0.15 Mn 0.7 O2 (abbreviated as NMZMO).
[0079] Comparative Example 2
[0080] A method for preparing a manganese-based positive electrode material for a sodium ion battery, which differs from Example 1 in that no Zn or Mg doping is performed, and no coating modification treatment is performed on the MnCO3 precursor, and specifically comprises the following steps:
[0081] S1. Synthesis of Precursors:
[0082] 10 mmol of manganese acetate tetrahydrate was weighed and dissolved in 80 mL of buffer solution (citric acid-sodium citrate buffer solution, pH value is 4.8-5.2) to form solution A, and stirred for reaction at room temperature for 2.5 hours; 15 mmol of anhydrous sodium carbonate (the molar amount of the precipitant is 1.5 times the molar amount of the manganese salt) was weighed and dissolved in 120 mL of deionized water to prepare a precipitant solution, and the precipitant solution was quickly poured into solution A, stirred for reaction at a heating temperature of 55°C for 7 hours, and centrifuged to collect a yellowish brown precipitate, which was thoroughly washed with deionized water and anhydrous ethanol, and dried in an oven at 80°C to obtain a MnCO3 precursor;
[0083] S2. High temperature roasting:
[0084] The MnCO3 precursor and sodium bicarbonate were weighed in a ratio of 1g:1.05g, and the MnCO3 precursor and sodium bicarbonate were ground and mixed evenly in a mortar, placed in a corundum calcining boat, and heated from room temperature to 750°C at a heating rate of 5°C / min, and calcined at 750°C in a pure oxygen atmosphere for 12h to obtain a manganese-based positive electrode material for sodium ion batteries as a blank control, with a chemical formula of Na 0.67 MnO2 (abbreviated as Bare-NMO).
[0085] The performance of the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested:
[0086] The positive electrode material powder was transferred to a vacuum oven to prepare a CR2032 button cell. First, 80 wt.% of the active material (positive electrode material powder) was mixed with 10 wt.% of carbon black and 10 wt.% of polyvinylidene fluoride. The obtained slurry was coated on an aluminum foil collector plate with a coating thickness of 50 ± 3 μm, and then dried at 60 ° C in a vacuum oven for 12 h; then, the obtained electrode sheet was perforated onto a disc with a diameter of 12 ± 3 mm and immediately transferred to a glove box filled with Ar atmosphere (O2 < 0.5 ppm, H2O < 0.5 ppm) for further use. The mass loading of the active material was 0.7 ± 0.03 mg cm -2 . With the above positive electrode as the working electrode, sodium metal as the reference counter electrode, 1MNaPF6 dissolved in dimethyl ether (DME) as the electrolyte, and glass fiber as the diaphragm, the R2032 coin-operated battery was assembled in a glove box filled with Ar atmosphere. The electrochemical performance of the material was tested using the BTS-5V10mA charge and discharge tester produced by Shenzhen Xinwell Company. The charge and discharge voltage range was 2.8V to 4.2V. The charge and discharge were carried out at room temperature at a rate of 0.1C. The capacity retention rate after 50 cycles of the battery and the capacity retention rate after 100 cycles of charge and discharge at a rate of 1C are shown in Table 1:
[0087] Table 1
[0088]
[0089] Comparison of the discharge capacity of the battery prepared in Example 1 and the battery prepared in Comparative Example 1 after 50 cycles at a rate of 0.1C. Figure 4 As shown; the discharge capacity of the battery prepared in Example 1 and the battery prepared in Comparative Example 2 after 100 cycles at 1C rate is compared. Figure 5 As shown,
[0090] From Table 1 and Figure 4 , Figure 5 It can be seen that the present invention obtains a co-doped precursor material by doping zinc and magnesium elements into manganese-based oxide. The addition of zinc and magnesium makes it have a wider lattice spacing, which reduces the Na + Diffusion is hindered during the charge and discharge process; the sodium aluminate formed on the surface of the material is evenly distributed, which inhibits the direct reaction of the positive electrode material with the electrolyte during the charge and discharge process; at the same time, the fast ion conductor coating can also improve the ionic conductivity of the material, effectively improving the battery's rate performance.
[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material, characterized in that: The following steps are involved: S1. Weigh soluble manganese salt, zinc salt and magnesium salt according to the molar ratio of the elements and dissolve them in a buffer solution, add a precipitant and mix well, heat the reaction and let it stand to obtain Zn x Mg y Mn 1-x-y CO3 precursor; S2. Dissolve the aluminum source in deionized water to obtain an aluminum source solution, and then add Zn x Mg y Mn 1-x-y The CO3 precursor is added to the aluminum source solution, and after being evenly dispersed, the solution is heated to react until the reaction is complete, filtered, and dried to obtain a coated and modified precursor; S3. The coated modified precursor and the sodium source are ground and mixed evenly, and then calcined to obtain a fast ion conductor coated sodium ion battery manganese-based positive electrode material with a chemical formula of NaAlO2@Na 0.67 Zn x Mg y Mn 1-x-y O2.
2. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 1, characterized in that: The manganese salt is manganese acetate, manganese sulfate or manganese chloride; the zinc salt is zinc acetate or zinc chloride; the magnesium salt is magnesium acetate or magnesium chloride; the precipitant is sodium carbonate or sodium bicarbonate; the aluminum source is aluminum chloride or aluminum sulfate; and the sodium source is sodium carbonate or sodium bicarbonate.
3. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 1, characterized in that: In S1, the molar amount of the precipitant is 1 to 2 times the total molar amount of the manganese salt, the zinc salt and the magnesium salt.
4. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 1, characterized in that: The heating temperature of the heating reaction in S1 and S2 is 50-60° C., and the reaction time is 2-8 hours.
5. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 1, characterized in that: In the S2, the aluminum source and Zn x Mg y Mn 1-x-y The dosage ratio of CO3 precursor is 0.5-1.5mmol:1g.
6. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 1, characterized in that: In S3, the amount of the sodium source used is 1.02-1.08 times the amount of the coated modified precursor.
7. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 1, characterized in that: The buffer solution in S1 is a citric acid-sodium citrate buffer solution with a pH value of 4.8-5.
2.
8. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 1, characterized in that: In the S3, the calcination temperature is 700-800° C., the calcination time is 5-20 hours, and the calcination atmosphere is oxygen.
9. The method for preparing a fast ion conductor coated sodium ion battery manganese-based positive electrode material according to claim 8, characterized in that: The heating rate during the calcination process is 1-10°C / min.
10. A fast ion conductor coated sodium ion battery manganese-based positive electrode material, characterized in that: Prepared by the preparation method described in claim 1.
Citation Information
Patent Citations
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN117059786A
Modified layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof
CN117393736A
Sodium-ion battery positive electrode material and preparation method thereof
CN117594785A
Preparation method for p2-type manganese-based sodium-ion battery positive electrode material
WO2023098168A1
Cited By
Manganese-based battery positive electrode material precursor and preparation method and application thereof
CN120398122A
Positive electrode precursor of high-capacity sodium battery as well as preparation method and application of positive electrode precursor
CN121627069A